2023
DOI: 10.7150/jca.86942
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the metabolism-related models for predicting prognosis and infiltrating immune phenotype in lung squamous cell carcinoma

Zeming Ma,
Liang Wang,
Xiaoyun Huang
et al.

Abstract: Purpose: Cancers often display disorder metabolism, which closely related to the poor outcome of patients. We aimed to establish prognostic models using metabolism-associated genes, and identify the key factor involved in metabolism in lung squamous cell carcinoma (LUSC). Materials and Methods: R package 'TCGA biolinks' was used to download the mRNA sequencing data of LUSC from TCGA. The clusterProfiler package was performed to analyze biological pathways. The online tool GEPIA2 and cox regression method were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Currently, neutrophils have received increasing attention for their pro-cancer effects, and an elevated neutrophil-to-lymphocyte ratio is considered a prognostic indicator for cancer (Xiong, Dong et al 2021). It was reported that the level of neutrophils in ltration was signi cantly increased in the group with high prognostic risk of LUSC (Ma, Wang et al 2023). In LUSC, neutrophil in ltration levels were also signi cantly positively correlated with other prognostic risk factors such as GLUT1 and DLD (Zhang, Dong et al 2022, Yang, Guo et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, neutrophils have received increasing attention for their pro-cancer effects, and an elevated neutrophil-to-lymphocyte ratio is considered a prognostic indicator for cancer (Xiong, Dong et al 2021). It was reported that the level of neutrophils in ltration was signi cantly increased in the group with high prognostic risk of LUSC (Ma, Wang et al 2023). In LUSC, neutrophil in ltration levels were also signi cantly positively correlated with other prognostic risk factors such as GLUT1 and DLD (Zhang, Dong et al 2022, Yang, Guo et al 2023).…”
Section: Discussionmentioning
confidence: 99%